2011
DOI: 10.1038/nature10609
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between deep fluids, tremor and creep along the central San Andreas fault

Abstract: Magnetotelluric data sense the electrical resistivity of the Earth, a physical parameter particularly sensitive to the presence of low resistivity phases such as aqueous fluids, partial melts or metallic compounds. Fluid phases have electrical resistivities orders of magnitude lower than the rock matrix, and thus relatively small amount of fluids, when interconnected, can decrease bulk rock resistivity by several orders of magnitude 9 .Fluids additionally have a significant weakening effect on the rheology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 43 publications
9
109
0
1
Order By: Relevance
“…They showed, using realistic fluid transport properties of the crust, that the fluid discharge rates from our model are sufficient to produce high fluid pressures in the seismogenic zone of the SAFS that approach lithostatic pressures. Becken et al (2011) show that electrical resistivity surveys measured across the SAF near Parkfield, California are consistent with vertical zones of low resistivity. Citing the Fulton and Saffer paper, Becken et al (2011) interpret these zones as representing fluid pathways where high-pressure fluids reduce resistance to frictional sliding.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…They showed, using realistic fluid transport properties of the crust, that the fluid discharge rates from our model are sufficient to produce high fluid pressures in the seismogenic zone of the SAFS that approach lithostatic pressures. Becken et al (2011) show that electrical resistivity surveys measured across the SAF near Parkfield, California are consistent with vertical zones of low resistivity. Citing the Fulton and Saffer paper, Becken et al (2011) interpret these zones as representing fluid pathways where high-pressure fluids reduce resistance to frictional sliding.…”
Section: Introductionmentioning
confidence: 82%
“…Becken et al (2011) show that electrical resistivity surveys measured across the SAF near Parkfield, California are consistent with vertical zones of low resistivity. Citing the Fulton and Saffer paper, Becken et al (2011) interpret these zones as representing fluid pathways where high-pressure fluids reduce resistance to frictional sliding. The present paper documents the modeling results that are, at least in part, the basis of interpretations in these later studies, and, in particular, the present paper documents the conceptual and numerical formulation of the model, and the rates of fluid discharge and the longevity of this source of pressurized water from our modeling results.…”
Section: Introductionmentioning
confidence: 82%
“…High conductivities in active tectonic zones have often been associated with fluids and hydrous minerals (Boerner et al 1998;Unsworth & Bedrosian 2004;Jones et al 2005;Ritter et al 2005;Wannamaker 2005;Becken et al 2011;Meqbel et al 2014). For instance, Becken et al (2011) interpreted a subvertical conductive anomaly extending through the entire crust northwest of Parkfield in California as a migration path for deep (partly mantle derived) fluids into the San Andreas Fault system. Signatures of mantle derived fluids in surface waters have been reported from major strike-slip faults around the world (e.g.…”
Section: Discussion O F T H E 2 -D E L E C T R I C a L C O Nmentioning
confidence: 99%
“…Ritter et al 2003Ritter et al , 2005Unsworth & Bedrosian 2004;Tank et al 2005;Thiel et al 2009;Becken et al 2011;Desissa et al 2013). The geometry and the overall conductance of FZCs depend on local geological, hydrogeological conditions and the geodynamic (tectonic) setting of a fault (see Unsworth & Bedrosian 2004;Ritter et al 2005, and references therein.).…”
Section: Discussion O F T H E 2 -D E L E C T R I C a L C O Nmentioning
confidence: 99%
“…A review of intraplate earthquakes in Japan found clear imaging of lowvelocity zones and/or high-Vp/Vs zones near the rupture sources of many major earthquakes (Hasegawa et al 2009), presumably related to the presence of lower crustal fluid; however, velocity structure alone is not sufficient to infer the presence of fluids. Geomagnetic surveys have found regions of low resistivity near many active faults, which could relate to the presence of fluids in the source area (Gupta et al 1996;Tank et al 2005;Wannamaker et al 2009;Becken et al 2011;Becken and Ritter 2012). In Japan, some close relationships between low-resistivity regions and earthquake faults have been proposed (Mitsuhata et al 2001;Yamaguchi et al 2001;Uyeshima et al 2005;Yoshimura et al 2008).…”
Section: Relationship Between Fluids From the Mantle And The Generatimentioning
confidence: 99%